Digital Water Accounting: A Comprehensive Research Report - Renaldo, Nicholas (Institut Bisnis dan Teknologi Pelita Indonesia, 2023)
Water accounting is essential for effective water resource management, involving systematic measurement, reporting, and verification. Traditional methods face limitations in accuracy, timeliness, and accessibility. Digital technologies have led to the emergence of digital water accounting systems, which offer more efficient, accurate, and real-time data management solutions. This research analyses the development, implementation, and impacts of these systems, evaluating their effectiveness and identifying associated benefits and challenges. A mixed-methods approach was employed, combining quantitative data from existing digital water accounting systems with qualitative interviews of water resource managers, technology providers, and policymakers. The study found that digital water accounting systems significantly improve water management through real-time data collection and automated reporting, enhancing accuracy and timeliness. They optimize water usage, reduce wastage, and improve allocation efficiency. However, challenges such as high costs, the need for technical expertise, and data security concerns remain. Digital water accounting advances water resource management by providing real-time, accurate, and accessible data, enhancing decision-making, efficiency, and stakeholder collaboration. To fully realize their potential, the study recommends investing in technology, establishing training programs, developing supportive policy frameworks, implementing robust data security measures, and fostering stakeholder collaboration and data sharing.